ANALYSIS OF STUDENTS’ COGNITIVE STRUCTURES USING FREE WORD-ASSOCIATION TEST IN CHEMISTRY LEARNING - Norma - Muningsih (LPPM Universitas Negeri Jakarta, 2018)
This study aims to determine the cognitive structure of high school students of class XI with free word-association method in teaching chemistry at the material buffer solution. The research was conducted in the second semester with a sample of 37 students at SMAN 89 Jakarta. The method used is qualitative in interpretivism paradigm, focused on the analysis of cognitive structures using free word-association method in teaching chemistry. Data obtained by interview, documentation, observation and student assignments through free word-association. Instruments free word-association tests contain stimulus word of